A semiotic and semantic study of Kain Punca Potong through pattern characteristic in Kelantanese weaving design - Ahmad, Nani Hartina (2022)
Kain Punca Potong is a long-woven cloth with two main features, namely the cloth body and the ends. It was an attire for Malays of the past who wore unstitched cloth wrapped around their bodies. The cloth was made famous since the reign of Kelantan’s Cik Siti Wan Kembang in the 17th century. It was widely worn by the Kelantan Malays around the 18th to late 19th centuries. Unfortunately, Kain Punca Potong production has started to decline with the lack of interest to learn its weaving techniques from the local generation. Until today, this precious cloth can only be found in galleries, museums, and private collections. It became an artifact too costly to own, due to lack of new productions. As seen in the statistics provided by the Malaysian Handicraft Development Corporation, the decline in weaving industry of Kelantan is getting dire by the days. Contrary to that, the cloth is still being used by national art heritage activists such as Malay high-end fashion activists who would don it during events and festivities as samping and scarfs. The research discovered that current society are not aware and did not fully comprehend the meaning behind the aspects of semiotic and semantic elements of character features in Kain Punca Potong design. This study tries to investigate the aspect of pattern design from the angles of semiotic and semantics through an observation on the cloth’s character features. Qualitative research method was performed for this study, where it is based on ethnography approach that employs interview, observation, and documentation techniques. The findings from these three techniques are combined in a triangulation form that incorporated descriptive approach to produce study data that is precise and comprehensive. In addition, the study are comprised of four phase, namely phase one: identification of main characteristic features; two: accumulation of in-depth data for analysis; three: design pattern formation, and lastly, phase four: findings and result will be used to create a IDEAL Guideline Framework for the production of Kain Punca Potong and to be verified by several experts of the field. The data was analyzed and subsequently assigned specific codes, categories, and theme that answers each of the study questions. The data collected were analyzed via Nvivo 12 application. Among the character features identified were design pattern formation design pattern types, and design pattern arrangement of Kain Punca Potong. Indeed, the character features present on Kain Punca Potong directly contributes to the Malay design elegance of the cloth. This study ultimately created a design guideline framework to guide designers and weavers in reproducing Kain Punca Potong with more detail, especially from the angles of semiotic and semantic approach to ensure the survival of Kain Punca Potong. With this, the nation’s weaving industry will further thrive.